Design and optimization of steam power systems in industrial parks based on the distributed steam turbine system - Zhang, Lingwei; Cui, Ziyuan; Wang, Yufei (Chinese journal of chemical engineering, 2025)
Steam power systems (SPSs) in industrial parks are the typical utility systems for heat and electricity supply. In SPSs, electricity is generated by steam turbines, and steam is generally produced and supplied at multiple levels to serve the heat demands of consumers with different temperature grades, so that energy is utilized in cascade. While a large number of steam levels enhances energy utilization efficiency, it also tends to cause a complex steam pipeline network in the industrial park. In practice, a moderate number of steam levels is always adopted in SPSs, leading to temperature mismatches between heat supply and demand for some consumers. This study proposes a distributed steam turbine system (DSTS) consisting of main steam turbines on the energy supply side and auxiliary steam turbines on the energy consumption side, aiming to balance the heat production costs, the distance-related costs, and the electricity generation of SPSs in industrial parks. A mixed-integer nonlinear programming model is established for the optimization of SPSs, with the objective of minimizing the total annual cost (TAC). The optimal number of steam levels and the optimal configuration of DSTS for an industrial park can be determined by solving the model. A case study demonstrates that the TAC of the SPS is reduced by 220.6×103 USD (2.21%) through the arrangement of auxiliary steam turbines. The sub-optimal number of steam levels and a non-optimal operating condition slightly increase the TAC by 0.46% and 0.28%, respectively. The sensitivity analysis indicates that the optimal number of steam levels tends to decrease from 3 to 2 as electricity price declines. [Display omitted]